2020
DOI: 10.1002/jbmr.4214
|View full text |Cite
|
Sign up to set email alerts
|

Sevelamer Use, Vitamin K Levels, Vascular Calcifications, and Vertebral Fractures in Hemodialysis Patients: Results from the VIKI Study

Abstract: BACKGROUND: Hyperphosphatemia is a risk factor for vascular calcifications (VCs) and VCs belong to mineral bone disorders (MBD) in chronic kidney disease (CKD) patients. Vitamin Kdependent proteins such as Matrix Gla Protein (MGP) and Bone Gla Proteins (BGP or osteocalcin) can inhibit VCs and regulate bone mineralization. OBJECTIVE: To evaluate whether the phosphate binder, sevelamer, could influence vitamin K levels in hemodialysis (HD) patients. METHODS: In a secondary analysis of the VItamin K Italian (VIKI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 70 publications
(188 reference statements)
1
15
1
1
Order By: Relevance
“…In a cross-sectional study of 387 hemodialysis patients (VItaminKItalian: VIKI study), Fusaro et al showed that MK-4 deficiency was the strongest predictor of aortic calcification (OR, 2.82; 95% CI, 1.14-7.01) [31]. In a secondary analysis, they found in patients treated with Sevelamer an odds ratio of MK-4 deficiency of 2.64 (95% CI 1.25-5.58, p = 0.01) [44]. Furthermore, sevelamer use significantly amplified the effect of total OC levels on the risk of VFs: BGP < 150 μg/L compared to those with total BGP ≥ 150 μg/L (OR 3.15, 95% CI 1.46-6.76, p = 0.003) [44].…”
Section: Vitamin K Status and Ckd-mbdmentioning
confidence: 99%
“…In a cross-sectional study of 387 hemodialysis patients (VItaminKItalian: VIKI study), Fusaro et al showed that MK-4 deficiency was the strongest predictor of aortic calcification (OR, 2.82; 95% CI, 1.14-7.01) [31]. In a secondary analysis, they found in patients treated with Sevelamer an odds ratio of MK-4 deficiency of 2.64 (95% CI 1.25-5.58, p = 0.01) [44]. Furthermore, sevelamer use significantly amplified the effect of total OC levels on the risk of VFs: BGP < 150 μg/L compared to those with total BGP ≥ 150 μg/L (OR 3.15, 95% CI 1.46-6.76, p = 0.003) [44].…”
Section: Vitamin K Status and Ckd-mbdmentioning
confidence: 99%
“…There are multiple studies addressing the potential consequences of sevelamer binding molecules beyond phosphate. Sevelamer may interfere with absorption of fat-soluble vitamins (D, K) [ 31 , 36 ] and has been associated with evidence of vitamin K deficiency, such as menaquinone MK4 deficiency and increased non-phosphorylated uncarboxylated matrix-Gla protein (dp-ucMGP) [ 39 , 40 ]. These defects were recently described in a cross-sectional study in association with a wider disturbance in uremic toxins of microbiota origin, including increased serum indoxyl sulfate (IS) and phenylacetylglutamine (PAG) in end stage kidney disease (ESKD), mostly dialysis, patients.…”
Section: Phosphate and Ckdmentioning
confidence: 99%
“…Vascular calcification (VC) is a useful marker of cardiovascular disease and several methods are available for the assessment of their presence and extension [1][2][3][4][5]. Although the pathogenesis of VC is not well established, several studies suggest that the prevalence of VC increases as renal function declines, likely due to the many metabolic abnormalities that characterize chronic kidney disease (CKD) [3,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…In these regards, the Kauppila score (KS) using lateral-lateral plain X-ray of the lumbar spine has been proposed to evaluate VC in the abdominal aorta. A few reports suggest a close correlation of KS and CAC as well as KS and risk of death in dialysis patients [1][2][3][4][5]. However, which VC measures best predicts long-term survival and whether a measure of vascular calcification adds to the predictive value of traditional Framingham risk stratification in incident to hemodialysis (HD) patients, has not been determined through a concurrent comparison of these measures in a single prospective cohort [5].…”
Section: Introductionmentioning
confidence: 99%